Large-Scale Scientific Computing: 10th International Conference, LSSC 2015, Sozopol, Bulgaria, June 8-12, 2015. Revised Selected Papers - Lirkov, Ivan D.; Margenov, Svetozar D.; Waśniewski, Jerzy (Lecture notes in computer science, 2015)
Multilevel Methods on Graphs -- Mathematical Modeling and Analysis of PDEs Describing Physical Problems -- Numerical Methods for Multiphysics Problems -- Control and Uncertain Systems -- Enabling Exascale Computation -- Efficient Algorithms for Hybrid HPC Systems -- Applications of Metaheuristics to Large-Scale Problems -- Computational Microelectronics — from Monte Carlo to Deterministic Approaches -- Large-Scale Models: Numerical Methods, Paralell Computations and Applications. .